Wound complications after common femoral vein endophlebectomy: Influence on outcome. (July 2018) - Gombert, Alexander; Barbati, Mohammad E; Grommes, Jochen; Kurstjens, Ralph LM; deWolf, Mark AF; Wittens, Cees HA; Jalaie, Houman
Introduction: Venous recanalization of obstructed femoral and iliac veins is associated with good results regarding the feasibility and patency rate. If the common femoral vein with its inflow vessels is involved, open surgical desobliteration or endophlebectomy has been described as a crucial part of the intervention. However, when performing the hybrid procedure, a number of specific complications have been described. We present our results after venous recanalization including an endophlebectomy, focussing on wound complications and its impact on outcome. Material and methods: A retrospective analysis of prospective recorded data of all patients who underwent a hybrid procedure for chronic obstruction of iliofemoral veins between 2010 and 2015 was performed. The patients were treated by recanalization of the affected veins combined with endophlebectomy of the common femoral vein and arteriovenous fistula implantation. Data assessment focussed on complications and patency rates. Results: This study includes 96 patients, thereof 58 females with a mean age of 44.1 years. The mean procedure time was 344 ± 140 min (range 124–663). Median follow-up time was 12.5 months (2–33 months). Primary patency was 62.5% and secondary patency was 90%. Re-intervention due to early occlusion within the first 30 post-intervention days was necessary in 37.5% of all cases. Besides bleeding complications, wound complications, mainly classified as Szilagyi I, occurred in 33% of all patients. A multivariate analysis showed a significant impact of wound complications on primary as well as secondary patency rate ( p = 0.032, respectively 0.015). Conclusion: Recanalization of obstructed iliac veins and/or the inferior vena cava combined with endophlebectomy of the common femoral vein and arteriovenous fistula implantation is a safe and feasible treatment option in the post-thrombotic syndrome. As wound complications are a common and associated with a significant impact on patency rate, further attempts to improve the procedure are crucial.